Detection of RET rearrangements in papillary thyroid carcinoma using RT-PCR and FISH techniques - A molecular and clinical analysis. Issue 6 (June 2019) - Musholt, Thomas Johannes; Staubitz, Julia Isabelle; Antonio Cámara, Rafael Jaime; Musholt, Petra Brigitta; Humberg, Diana; Springer, Erik; Schad, Arno
Abstract: Introduction: Oncogenic BRAF and RAS mutations as well as multiple known (and yet unknown) RET fusion oncogenes comprise the majority of causative molecular alterations in papillary thyroid carcinoma (PTC). Apparently "mutation-negative" PTCs encompass a heterogenous group impeding analysis of prognostic significance of underlying genetics. Material and methods: BRAF wild type PTC tissue of 56 patients was analyzed using two established methods: hybrid-specific RT-PCR for the predominant rearrangement RET/PTC1 and fluorescent in situ hybridization (FISH). Clinical features of the cases with and without RET rearrangement were compared (patient age, gender, tumor size, focality, lymph node affection, and iodine avidity). Results: RT-PCR revealed RET/PTC1 rearrangements in five of 56 tumors (9%). FISH confirmed these, and identified four additional RET rearrangements (9/56; 16%). Loss of the iodine avidity only occurred in cases of RET/PTC hybrids (7/9 tumors), but not in RET/PTC-negative PTCs (0/41 tumors with available uptake information; p = 0.029). The risk to develop lymph node metastases was eight times higher in presence of RET rearrangements (p = 0.010). Conclusions: FISH analysis, in contrast to hybrid-specific RT-PCR, revealed infrequent and unknown RET fusion genes. The presence of RET rearrangements was associated with a significantly elevated risk to develop iodine refractory disease and lymph node metastases. Of note, significant clinical discrimination was only achievable when taking the FISH results into account; differences would have been missed when using the RT-PCR method only. Increasing evidence of the clinical impact of RET/PTC-positivity may influence the decision on the extent of surgical resection, especially on lymph node dissection, in PTCs.